A study on utilization, storage and stabilization of rice bran - Villarino, Blanca Jucar; Mateo, Ma. Liwayway T. (1993.)
The study was conducted for the purpose of utilizing rice bran as a human food source. Specifically, this study aimed to substitute rice bran for wheat flour in muffins. Different levels of substitution, 10%, 20%, and 30% were studied. The optimum method of stabilizing rice bran was also determined. Shelf-life estimation of the product resulting from the aforementioned studies with physico-chemical and sensory monitoring were also performed. Among the samples containing rice bran, the 20% level of incorporation was found to be the optimum level, as supported by the results of objective and sensory analyses. At this level, nutrient contribution of rice bran in muffins was also determined to be favorable. Stabilization and storage studies pointed out to the moist-heat stabilization method as the more effective way of stabilizing rice bran. This is supposed by the result of shelf-life estimation: 70.11 days for moist-heat stabilized bran and 56.5 days for the dry-heat stabilized bran. Also, the latter developed deteriotative factors such as free fatty acids and moisture at a faster rate than the moist-heat stabilized bran.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Rice bran